Cultures of Environmental Communication A Multilingual Comparison - Nofri, Sara. (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer VS, 2013)
Sara Nofri combines several research methods (multilingual bibliographic research, quantitative content analysis, semiotic text analysis, interviews to journalists) and a cross-cultural, interdisciplinary perspective for investigating environmental communication in the daily quality press of Germany, Italy, Sweden and UK. She provides an in-depth portrait of the features, the focus, the themes and stakeholders involved, individuates different "cultures of environment" and "cultures of communication", and provides insights and practical tools to analyze and then evaluate environmental communication. The methodological approach of this study can be readily transposed to studies investigating other contexts, cultures and media.   Der Inhalt ·        Environmental Communication in the Press ·        European Media Comparison ·        Cultures of Environment ·        Cultures of Communication ·        Interdisciplinary and Cross-Cultural Study ·        Multilingual Information Retrieval and Research     Die Zielgruppen ·        Researchers, scholars, and students in the fields of communication science, journalism, media and cultural studies, and environmental studies, among others. ·        Environmental journalists and communicators, lobbyists and activists, policy makers.   Die Autorin Dr. Sara Nofri completed her doctoral project under the supervision of Prof. Hans J. Kleinsteuber at the University of Hamburg and is currently working as an international media analyst and researcher, with a focus on digital media.
SpringerLink eBooks.
Keywords: Social sciences; Communication; Social Sciences; Social Sciences, general; Communication Studies